Continuity of Care in Swiss Cancer Patients Using Claims Data - Blozik, Eva (Patient Prefer Adherence, 2020)
BACKGROUND: Continuity of care is positively associated with beneficial patient outcomes. Data on the level of continuity of care in the ambulatory setting in Switzerland are lacking. AIM: The aim of this study was to evaluate continuity of care in Swiss cancer patients based on routine data of mandatory health insurance using four established continuity scales. METHODS: Retrospective analysis of Swiss claims data (N=23ʹ515 patients with incident use of antineoplastics). The Usual Provider Continuity score, the Modified Modified Continuity Index, the Continuity of Care index, and the Sequential Continuity Index were analyzed based on consultations with general practitioners (GPs), physician specialists and ambulatory hospital wards. RESULTS: Using information of health insurance claims, the number of consultations and the general level of continuity of care in Swiss cancer patients are high. Continuity of care scores were significantly associated with sociodemographic and regional factors. When focusing on consultations with GPs only, all four scores consistently showed high values indicating high levels of continuity. Continuity with general practitioners was associated with lower costs and lower risks for hospitalization and death. CONCLUSION: This is the first study giving insight into continuity of care in Swiss cancer patients. The present study shows that continuity of care is measurable using health insurance claims data. It indicates that continuity with general practitioners is associated with a beneficial outcome.